2014
DOI: 10.7150/thno.7851
|View full text |Cite
|
Sign up to set email alerts
|

PI3K-AKT-mTOR-Signaling and beyond: the Complex Network in Gastroenteropancreatic Neuroendocrine Neoplasms

Abstract: Gastroenteropancreatic neuroendocrine neoplasms are heterogeneous in their clinical behavior and require therapies specially tailored according to staging, grading, origin and expression of peptide receptors. Despite extensive scientific efforts, the therapy options are still not satisfactory. The main reasons are due to the lack of a broad mechanistic knowledge, an insufficient classification of specific diagnostic sub-groups, and predictive markers. GEP-NEN tumors evade early diagnosis because of slow asympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 506 publications
(296 reference statements)
4
74
1
Order By: Relevance
“…Therefore, miR302a may have targeted p-ERK1/2 and p-Akt through the MAPK and PI3K signaling pathways, respectively, and this may be its primary contribution to the inhibition of cell proliferation in TE-10 and ECA109 cells. Consistent with previous results, in the present study, the phosphorylation levels of Akt and ERK1/2 were significantly decreased in the miR302a mimics group (P<0.05), and increased in the miR302a inhibitor group (P<0.01) (23)(24)(25)(26). Furthermore, total Akt and ERK1/2 expression levels were also determined by western blot analysis in TE-10 and ECA109 cells, and overexpression of miR302a did not markedly differ between groups.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, miR302a may have targeted p-ERK1/2 and p-Akt through the MAPK and PI3K signaling pathways, respectively, and this may be its primary contribution to the inhibition of cell proliferation in TE-10 and ECA109 cells. Consistent with previous results, in the present study, the phosphorylation levels of Akt and ERK1/2 were significantly decreased in the miR302a mimics group (P<0.05), and increased in the miR302a inhibitor group (P<0.01) (23)(24)(25)(26). Furthermore, total Akt and ERK1/2 expression levels were also determined by western blot analysis in TE-10 and ECA109 cells, and overexpression of miR302a did not markedly differ between groups.…”
Section: Discussionsupporting
confidence: 79%
“…A small, aggressive subgroup shows high proliferation rates, but most GEP-NENs demonstrate slow-growing characteristics, which makes them inaccessible to classical chemotherapies [1] . Despite their increasing incidence, GEP-NENs are counted among the rare neoplastic diseases.…”
Section: Current Therapy Options For Gastroenteropancreatic Neuroendomentioning
confidence: 99%
“…Mutations in the PI3K pathway components were found in human cell lines that respond to rapalogs in terms of antiproliferative effects (Di Nicolantonio et al 2010). The PIK3CA gene, however, is rarely mutated in pNETs (Jiao et al 2011) and PI3K-p85a subunit mutations as well as PI3K amplifications have not been reported in NETs, so far (Briest & Grabowski 2014). Data on KRAS mutations in pNETs are also controversial: none of the 44 pNETs belonging to a Caucasian cohort was found to harbour KRAS somatic mutations (Gilbert et al 2013), which were on the contrary reported in four out of 37 consecutive Chinese pNET patients (Yuan et al 2014).…”
Section: Methodsmentioning
confidence: 99%